KINERJA SUMBER DAYA MANUSIA BERBASIS POLA KERJA CERDAS DAN KUALITAS KOMUNIKASI DENGAN MODERASI PENGAWASAN - Diyah Sismartini; Moch. Ali Shahab (Jurnal Riset Bisnis Indonesia, 2016)
This research was conducted in order to test and analyze Performance Based human ResourcesPattern of Smart Working and Quality Communication with Moderation Controlling (Studies inFunctional Extension in Women Empowerment and Family Planning Batang) the total sample of75 people. Data collection techniques was done by the technique of “census”. Tests using Analysisof Partial Least Square (PLS). The research concludes that the communication quality is higher,the higher the performance of human resources. Patterns smart working is higher, the higher theperformance of human resources. The higher the communication quality, the higher the performanceof human resources without moderation controlling. Patterns smart working is higher, the higher theperformance of human resources without moderation controlling. The test results showed that thesurveillance is not a moderating variable.Keywords: Quality Communication, Smart Working, Controlling, and Performance f HumanResources..